Studi Epidemiologi Kematian Ibu di Provinsi Sumatera Selatan pada Masa Pandemi Covid-19: Literatur Riview - Najmah Najmah; Chairil Anwar; Muhammad Ridho Sadewa (Universitas Batanghari Jambi, 2023)
Maternal Mortality (MMR) is an indicator of the success of a country's services. Every day around 830 women die from preventable causes related to pregnancy and childbirth. To review the determinants of maternal mortality in South Sumatra Province during the Covid-19 pandemic. This research uses a literature study approach from several databases such as sinta, pubmed, South Sumatra Province Health Profile and google scholar, by carrying out a narrative synthesis of the main search for maternal death during the co-19 pandemic. Factors that can cause maternal death. Family planning can reduce the total risk of death in women due to pregnancy. This is not a problem to reduce the risk for those who are pregnant. The role of family planning in combating maternal mortality is to help create healthy conditions for childbirth and reduce the risk of pregnancy-related death for women. this is only one part of a complex answer to a complex problem. Based on the analysis that has been carried out is maternal mortality during the Covid-19 pandemic. This article uses the method of literature review from scientific journals guided by keywords. There are 4 selected scientific journals, each journal representing this research, one of which is a determinant of the causes of maternal death during the Covid-19 pandemic. Maternal mortality during the Covid-19 pandemic is a complex problem that needs serious treatment in an effort to prevent complications that may occur during pregnancy and childbirth so as to reduce maternal mortality. Based on the analysis that has been carried out is to protect reproductive rights and human rights by reducing the burden of morbidity, disability and death associated with pregnancy and childbirth that should not have happened with the Safe Motherhood and Making Pregnancy Safer programs.